Influence of Internal and External Characteristics of Agricultural Extensionist on Internet Media Utilization - Muhammad Thamrin; Jabal Tarik Ibrahim; Sutawi Sutawi; Wan Arfiani Barus (International Journal Reglement & Society (IJRS), 2023)
The presence of information technology is a challenge for field agricultural extension to master computer skills and utilize the internet. The purpose of this study was to determine the performance of field agricultural extension and the effect of internal and external characteristics of extension on the utilization of internet media in Deli Serdang Regency. The population and research sample were 139 people using the census method. This study uses Pearson product moment correlation, multiple regression analysis, and effective contribution testing. The results of simultaneous correlation and regression tests through the F test show that there is a significant relationship and influence between each variable. Partially in multiple regression tests, the variables of age, education level, internet media ownership, perception of the internet, and internet usage patterns have a significant effect, while the variable of agency support has no significant effect on internet media utilization for extension. Based on the calculation of effective contribution, the variable internet usage pattern shows the largest effective contribution of 19.87 % with a relative contribution of 39.15 %..